2014
DOI: 10.1007/s10661-014-4035-8
|View full text |Cite
|
Sign up to set email alerts
|

Pristine aquatic systems in a Long Term Ecological Research (LTER) site of the Brazilian Cerrado

Abstract: The maintenance of limnological monitoring programs in the Cerrado Domain is crucial as a provision of useful information about temporal variations in land use and their respective water quality responses, considering its importance as water source for different Brazilian hydrographic basins. The purpose of this research was to describe limnological variables of low-order lotic systems located in the Cerrado Long Term Ecological Research (LTER) site (Environmental Protection Area (APA) Gama and Cabeça de Veado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Extremely weathered, undisturbed watersheds are characterized by very low in-stream ionic concentrations z z z Figure 6. For pristine Cerrado streams, Fonseca et al (2013) and Fonseca and de Mendonça-Galvão (2014) found very low nutrient baselines for first to third streams compared with other natural areas in Brazil or temperate regions. The published value is averaged over the depth.…”
Section: Alteration Of Water Quality In the Cerradomentioning
confidence: 82%
See 1 more Smart Citation
“…Extremely weathered, undisturbed watersheds are characterized by very low in-stream ionic concentrations z z z Figure 6. For pristine Cerrado streams, Fonseca et al (2013) and Fonseca and de Mendonça-Galvão (2014) found very low nutrient baselines for first to third streams compared with other natural areas in Brazil or temperate regions. The published value is averaged over the depth.…”
Section: Alteration Of Water Quality In the Cerradomentioning
confidence: 82%
“…Thus, Markewitz et al (2006) showed for second-order streams that most measured ionic components (Ca 2+ , Mg 2+ , K + , Na 2+ , Cl À , SO 4 2À and alkalinity), excluding NH 4 + -N and NO 3 À N, show a seasonal variation: high values in the dry season were at least three times larger in the wet season. For pristine Cerrado streams, Fonseca et al (2013) and Fonseca and de Mendonça-Galvão (2014) found very low nutrient baselines for first to third streams compared with other natural areas in Brazil or temperate regions. The authors concluded that the response to anthropogenic impacts was slower in these regions than in the Amazon.…”
Section: Alteration Of Water Quality In the Cerradomentioning
confidence: 82%
“…(1) they respond to changes in the aquatic environment and in the adjacent terrestrial ecosystems(Álvarez-Cabria et al 2016;Lei et al 2020);(2) they are easily and inexpensively measurable; (3) they are useful to develop data bases representing pristine conditions(Fonseca and Mendonça-Galvão 2014), and (4) are useful…”
mentioning
confidence: 99%
“…Although more data are available from local and regional studies by local water managers or environmental protection agencies, they are not published in scientific journals and thus the impacts of land use on aquatic systems, that is, pollution from nutrients and pesticides, their in-stream processes, and their effects on aquatic habitats, are not well understood (Hunke et al, 2015a). Biome-specific water quality thresholds lack in Brazil (Hunke et al, 2015b), except for baselines for physical-chemical water parameters ranging from natural to very impacted conditions in the Cerrado area reported by Fonseca et al (2014).…”
mentioning
confidence: 99%